Effects of carnitine on adipose metabolism in Chinese soft-shelled turtles - ZHAN Xiu-an; XU Zi-rong (浙江大学学报. 农业与生命科学版, 2002)
One thousand one hundred and seventy Chinese soft-shelled turtles allotted to three groups by weight and sex were conducted to study the effects of carnitine on adipose metabolism. Every group included three replicates of one hundred and thirty turtles each. The groups received the same basal diet supplemented with 0, 50, 100 l-carnitine respectively during the period of 211 to 360 day ages. The results showed that 100 mg/kg l-carnitine treated group was the most effective, which decreased the weight of fat deposited in extremities by 27.11% (P<0.01). Data from samples analyses indicated that adding 100 mg/kg l-carnitine significantly increased activity of malic dihydrogenase of liver and fat by 24.32% (P<0.01) and 32.22% (P<0.01), and that of hormone-sensitive lipase of fat by 14.88% (P<0.05), and that of lipoprotein lipase of muscle and fat by 27.08% (P<0.01) and 13.18% (P< 0.05), and the content of free carnitine and total acid-insoluble cartinine of muscle by 16.92% (P< 0.01) and 38.24% (P<0.01).